Kausalitas Teknologi, Pendidikan dan Penyerapan Tenaga Kerja di Sumatera Barat - Triadi, Hendra; Anis, Ali (Universitas Negeri Padang, 2023)
This study aims to identify and analyze the causal relationship between technology (Y1), education (Y2) and labor absorption (Y3) variables in West Sumatra Province. This type of research is associative and descriptive which explains whether or not there is a causal relationship between research variables. The data used in this study are secondary data from 2011 to 2020 according to districts/cities in West Sumatra Province obtained from related agencies. The analysis in this study uses the Panel Vector Autoregression (PVAR) model with a causality test using the Granger Causality Test and the cointegration test in this study uses the Kao Residual Cointegration Test method. The research results obtained show that: (1) Technology and education do not have a causal relationship, but there is a one-way causality relationship, namely education to technology in West Sumatra Province. (2) Education and employment do not have a causal relationship in West Sumatra Province. (3) Technology and employment do not have a causal relationship in West Sumatra Province.